Fabrication of Microstructures Embedding Controllable Particles inside Dielectrophoretic Microfluidic Devices. (15th February 2013) - Yue, Tao; Nakajima, Masahiro; Tajima, Hirotaka; Fukuda, Toshio
This paper presents a method of particle manipulation by dielectrophoresis (DEP) and immobilization using photo-crosslinkable resin inside microfluidic devices. High speed particle manipulation, including patterning and concentration control by DEP was demonstrated. Immovable and movable microstructures embedding particles were fabricated on-chip. Several microelectrodes were fabricated using Indium Tin Oxides (ITO) and Cr/Au. The two kinds of DEP responses of yeast cells ( W303 ) and other particles were experimentally confirmed. Based on negative DEP phenomenon, cell traps generated by microelectrodes were demonstrated. Position control, transportation and patterning of cells were performed with cell traps. The on-chip fabrication of arbitrary shapes of microstructures based on Poly(ethylene glycol) diacrylate (PEGDA) was reported. With cell patterning by DEP and immobilization using on-chip fabrication, microstructures embedding line patterned cells were fabricated inside microfluidic channels. A novel microfluidic device was designed to separate patterning and fabrication areas and movable microstructures embedding concentration controllable particles were fabricated inside this device.